Feeding incremental amounts of the red seaweed Chondrus crispus: Effects on production performance, methane emissions, nutrient utilization, and ruminal and iodine metabolism in dairy cows - D.C. Reyes; J.P. Sacramento; C.T.C. Quigley; B.S. Twining; A.B. Michaud; D. Emerson; B. Honisch; O. Keleher; M.A. Rahman; N.N. Price; A.F. Brito (Journal of Dairy Science, 2025)
ABSTRACT: We investigated the effects of feeding incremental amounts (0%, 3%, and 6% of diet DM) of the red seaweed Chondrus crispus on DMI, milk yield and milk components, enteric CH4 emissions, nutrient utilization, ruminal fermentation and microbiota relative abundance, and I metabolism in dairy cows. Eighteen organic certified Jersey cows (12 multiparous and 6 primiparous) averaging (mean ± SD) 94 ± 45 DIM, 22 ± 5.2 kg of milk/d, and 485 ± 54 kg of BW in the beginning of the study were used in a replicated Latin square design with three 24-d periods (14 d for diet adaptation and 10 d for data and sample collection). Diets were fed as TMR, with the control treatment (0% C. crispus) consisting of (DM basis) 60% mixed-mostly grass baleage and 40% ground corn-soybean meal-based concentrate mash, with forage and grain (up to 2.1% each) replaced by 3% and 6% C. crispus in the remaining 2 diets. Feeding increasing amounts of C. crispus linearly decreased DMI and daily BW gain. However, no linear or quadratic effect was observed for the concentrations and yields of milk fat, true protein, and lactose, and the yields of milk, 4% FCM, and ECM. The concentration of MUN showed a quadratic response (lowest in the 3% C. crispus diet), and that of plasma urea N decreased linearly with feeding increasing levels of C. crispus. Similarly, enteric CH4, CO2, and H2 production all decreased linearly in cows fed C. crispus. In contrast, no linear or quadratic effect was detected for CH4 yield and CH4 intensity. Whereas energy loss as CH4 and heat production decreased linearly, energy efficiency utilization variables did not respond linearly or quadratically to supplementation with C. crispus. The apparent total-tract digestibilities of OM and NDF, and the urinary excretion of urea N (% of N intake) and uric acid tended to decrease linearly with C. crispus. The ruminal molar proportion of acetate increased quadratically, and that of isovalerate decreased linearly in response to C. crispus inclusion in the diet DM. No linear or quadratic effect was observed for the relative abundance of most ruminal microbiota taxa. Iodine intake, milk I concentration and yield, and fecal I excretion increased linearly, and urinary I excretion increased quadratically in cows fed C. crispus, with no linear or quadratic effect in the plasma concentrations of thyroid hormones and whole blood cell composition. Overall, increasing dietary levels of C. crispus decreased DMI and enteric CH4 production linearly without compromising milk yield and milk composition.